An analysis of environment, microphone and data simulation mismatches in robust speech recognition. (November 2017) - Vincent, Emmanuel; Watanabe, Shinji; Nugraha, Aditya Arie; Barker, Jon; Marxer, Ricard
Highlights: An analysis of the impact of acoustic mismatches between training and test data on the performance of robust ASR. Including: environment, microphone and data simulation mismatches. Based on: a critical analysis of the results published on the CHiME-3 dataset and new experiments. Result: with the exception of MVDR beamforming, these mismatches have little effect on the ASR performance. Contribution: the CHiME-4 challenge, which revisits the CHiME-3 dataset and reduces the number of microphones available for testing. Abstract: Speech enhancement and automatic speech recognition (ASR) are most often evaluated in matched (or multi-condition) settings where the acoustic conditions of the training data match (or cover) those of the test data. Few studies have systematically assessed the impact of acoustic mismatches between training and test data, especially concerning recent speech enhancement and state-of-the-art ASR techniques. In this article, we study this issue in the context of the CHiME-3 dataset, which consists of sentences spoken by talkers situated in challenging noisy environments recorded using a 6-channel tablet based microphone array. We provide a critical analysis of the results published on this dataset for various signal enhancement, feature extraction, and ASR backend techniques and perform a number of new experiments in order to separately assess the impact of different noise environments, different numbers and positions of microphones, or simulated vs. real data on speech enhancement and ASR performance. We show that, with the exception of minimum variance distortionless response (MVDR) beamforming, most algorithms perform consistently on real and simulated data and can benefit from training on simulated data. We also find that training on different noise environments and different microphones barely affects the ASR performance, especially when several environments are present in the training data: only the number of microphones has a significant impact. Based on these results, we introduce the CHiME-4 Speech Separation and Recognition Challenge, which revisits the CHiME-3 dataset and makes it more challenging by reducing the number of microphones available for testing.